(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article examines the role of mathematical modeling in developing intuitive thinking among cadets in higher military education. The study analyzes how intuition and analytical reasoning interact during the process of constructing and solving real military problems. Using practical examples —artillery targeting, optimization of logistics, and probabilistic decision models —the paper demonstrates how mathematical modeling enhances cadets’ independent thinking, creativity, and the ability to make strategic decisions in uncertain environments.